Introduction to engineering economy - Fleischer, G. A. (Boston, Massachusetts : PWS Publishing Company, 1994)
This book may be used as either a primary or secondary source in a first course in engineering economy, financial management, capitla budgeting, managerial economics, adn the like.
1. Introduction -- 2. Equivalence and the Mathematics of Compound Interest -- 3. Measures of Worth I: Ranking of Alternatives by Increasing/Decreasing Equivalent Worth Measures -- 4. Measures of Worth II: Ranking of Alternatives by Marginal (Incremental) Analysis -- 5. Measures of Worth III: Some Additional Methods for Determining Economic Value -- 6. Depreciation and Certain Other Noncash Expenses -- 7. Taxes and After-Tax Economy Studies -- 8. Retirement and Replacement -- 9. Revenue Requirement Method -- 10. Economic Risk Analysis -- 11. Incorporating Price-Level Changes (Inflation) into the Analysis -- Appendix A: Summary of Notation -- Appendix B: Compound Interest Tables.
Includes bibliographical references and index.
Keywords: ENGINEERING ECONOMY